Neurofilament light and heavy subunits compared as therapeutic biomarkers in multiple sclerosis. (13th June 2013) - Kuhle, J.; Malmeström, C.; Axelsson, M.; Plattner, K.; Yaldizli, Ö.; Derfuss, T.; Giovannoni, G.; Kappos, L.; Lycke, J.
Abstract : Background: Neurofilaments are promising biomarkers in multiple sclerosis (MS) and increased levels in cerebrospinal fluid (CSF) indicate axonal damage or degeneration. In a previous study, neurofilament light chain (NfL) levels in CSF of relapsing remitting (RR) patients with MS were normalized by natalizumab treatment. Aims of the study: We compared the coherence between NfL and neurofilament heavy chain (NfH SMI 35 ) levels in longitudinal CSF samples in a subset of these patients. Methods: In 30 patients with RRMS, CSF was obtained prior to and following 12 months of natalizumab treatment. NfH SMI 35 was measured by an electrochemiluminescence‐based immunoassay. NfL levels were determined previously by the UmanDiagnostics NF‐light ® assay. Results: NfH SMI 35 decreased in 73.3% and NfL in 90% of the patients following natalizumab treatment (32.4 vs 27.4 pg/ml, P  = 0.002 and 820 vs 375 pg/ml, P  < 0.0001). Patients experiencing a relapse showed higher NfH SMI 35 levels compared with patients in remission (47.7 vs 27.6 pg/ml, n  = 8, P  = 0.001). This difference was less obvious for NfL (1055 vs 725 pg/ml, P  = 0.256). In patients in remission, NfL levels were lower following natalizumab treatment (830 vs 365 pg/ml, n  = 20, P  = 0.0002), whereas the same comparison failed significance for NfH SMI 35 (28.3 vs 26.9 pg/ml, P  = 0.086). Conclusions: We confirm previous findings, indicating reduced axonal damage under natalizumab treatment by measuring NfH SMI 35, using an assay with independent methodology. In comparison with NfH SMI 35, NfL changes were more pronounced and the treatment effect also included patients in remission. Our results suggest that NfL is superior over NfH SMI 35 as therapeutic biomarker and is a promising candidate to measure neuroaxonal damage in MS treatment trials.